2014
DOI: 10.1091/mbc.e14-02-0702
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fusion properties of synaptotagmin-1 and synaptotagmin-7 bearing dense core granules

Abstract: Adrenal chromaffin cells express two synaptotagmin isoforms, Syt-1 and Syt-7. Isoforms are usually sorted to separate secretory granules, are differentially activated by depolarizing stimuli, and favor discrete modes of exocytosis. It is proposed that stimulus/Ca+-dependent secretion in the chromaffin cell relies on selective Syt isoform activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
92
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 58 publications
18
92
1
Order By: Relevance
“…Synaptotagmin isoforms have different affinities for calcium, suggesting that they could mediate exocytosis of distinct vesicle pools in vivo [125]. Sorting of Syt-1 and Syt-7 onto distinct vesicle pools occurs in chromaffin cells and affects exocytotic behavior [127]. …”
Section: What Are the Local Exocytotic Protein Targets Of Pkc?mentioning
confidence: 99%
See 3 more Smart Citations
“…Synaptotagmin isoforms have different affinities for calcium, suggesting that they could mediate exocytosis of distinct vesicle pools in vivo [125]. Sorting of Syt-1 and Syt-7 onto distinct vesicle pools occurs in chromaffin cells and affects exocytotic behavior [127]. …”
Section: What Are the Local Exocytotic Protein Targets Of Pkc?mentioning
confidence: 99%
“…For example, phosphorylation of synaptotagmin-7 by PKC would enhance its affinity for the SNARE complex and consequently enhance docking of synaptotagmin-7-labeled vesicles with the plasma membrane. This could lead to a change in the apparent calcium sensitivity of exocytosis, as synaptotagmin-7 has a higher calcium affinity than synaptotagmin-1 [127]. Consistent with a scenario under which different synaptotagmin isoforms are relevant PKC targets in different cellular systems, Nagy et al showed in chromaffin cells that overexpression of synaptotagmin-1 phosphomutants and phosphomimetics did not appear to alter exocytosis, whereas in another system, hippocampal neurons, phosphomimetics of synaptotagmin-1 regulate exocytosis [73, 130].…”
Section: What Are the Local Exocytotic Protein Targets Of Pkc?mentioning
confidence: 99%
See 2 more Smart Citations
“…A 2014 study by Anantharam’s group indicated that the two synaptotagmin isoforms expressed in chromaffin cells, synaptotagmin-1 (Syt-1) and Syt-7, are located on distinct populations of chromaffin secretory granules (2). This dovetails with other data showing differences among synaptotagmins.…”
mentioning
confidence: 99%